Ex situ Ge-doping of CZTS nanocrystals and CZTSSe solar absorber films. (13th July 2022) - Naylor, Matthew C.; Tiwari, Devendra; Sheppard, Alice; Laverock, Jude; Campbell, Stephen; Ford, Bethan; Xu, Xinya; Jones, Michael D. K.; Qu, Yongtao; Maiello, Pietro; Barrioz, Vincent; Beattie, Neil S.; et al.
Abstract : Ge doping is employed to aid the recrystallisation of Cu2 ZnSnS4 nanocrystals. Opto-electrical properties are presented to describe Ge incorporation with a focus on the electronic interface between the Ge:Cu2 ZnSn(S, Se), absorber and CdS buffer layer. Abstract : Cu2 ZnSn(S, Se)4 (CZTSSe) is a promising material for thin-film photovoltaics, however, the open-circuit voltage ( V OC ) deficit of CZTSSe prevents the device performance from exceeding 13% conversion efficiency. CZTSSe is a heavily compensated material that is rich in point defects and prone to the formation of secondary phases. The landscape of these defects is complex and some mitigation is possible by employing non-stoichiometric conditions. Another route used to reduce the effects of undesirable defects is the doping and alloying of the material to suppress certain defects and improve crystallization, such as with germanium. The majority of works deposit Ge adjacent to a stacked metallic precursor deposited by physical vapour deposition before annealing in a selenium rich atmosphere. Here, we use an established hot-injection process to synthesise Cu2 ZnSnS4 nanocrystals of a pre-determined composition, which are subsequently doped with Ge during selenisation to aid recrystallisation and reduce the effects of Sn species. Through Ge incorporation, we demonstrate structural changes with a negligible change in the energy bandgap but substantial increases in the crystallinity and grain morphology, which are associated with a Ge–Se growth mechanism, and gains in both the V OC and conversion efficiency. We use surface energy-filtered photoelectron emission microscopy (EF-PEEM) to map the surface work function terrains and show an improved electronic landscape, which we attribute to a reduction in the segregation of low local effective work function (LEWF) Sn(ii ) chalcogenide phases.